2012
DOI: 10.5923/j.ije.20120203.01
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Water Arsenic and Boron Pollutants and Algae Phytoremediation in Three Springs, Iran

Abstract: Today drinking water quality, water pollutant and cleaning water are important topics in applied hydrology.Algae play an important role in controlling metal concentration in lakes and oceans. Their ability to absorption metals and taking up toxic elements from the environment has been recognized for many years. The study is examination of the possible extent of Arsenic and Boron algae phytoremediation in three springs from Sang-E-Noghreh area, Iran, by calculating bio-concentration and bio-accumulation factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Contamination with heavy metals had shown inhibition of nitrogen fi xation of by the strain of Rhizobium leguminosarum in Trifolium repens (Hirsch et al 1993 ) and in faba bean (Chaudri et al 2000 ). The reduction in the activity of nitrogenase in fi eld and pot trials with decreased nodulation, nitrogen metabolism, and plant growth was also reported (Ahmad et al 2012 ). Besides, heavy metals at toxic level interfere the induction of root hairs, mineral absorption, normal metabolism, and growth morphology.…”
Section: Heavy Metals Cadmium and Biological Functionsmentioning
confidence: 79%
See 1 more Smart Citation
“…Contamination with heavy metals had shown inhibition of nitrogen fi xation of by the strain of Rhizobium leguminosarum in Trifolium repens (Hirsch et al 1993 ) and in faba bean (Chaudri et al 2000 ). The reduction in the activity of nitrogenase in fi eld and pot trials with decreased nodulation, nitrogen metabolism, and plant growth was also reported (Ahmad et al 2012 ). Besides, heavy metals at toxic level interfere the induction of root hairs, mineral absorption, normal metabolism, and growth morphology.…”
Section: Heavy Metals Cadmium and Biological Functionsmentioning
confidence: 79%
“…Rawat et al ( 2011 ) have recognized microalgae as the most promising organism for bioprocess due to multiplicity of reactions. Mitra et al ( 2012 ) have reported four algal divisions, viz., chlorophyta, cyanophyta, euglenophyta, and heterokontophyta as accumulators of boron and arsenic. Chara vulgaris is observed for strong phytoextraction ability of Congo red dye from its aqueous solution.…”
Section: Algae In Phytoremediationmentioning
confidence: 99%
“…Simply, it refers to utilize green plants to remove contaminants from soil and water (Mitra, 2012). It is cost effective, as ethically accepted, and it is less disturbed to the environment.…”
Section: Phytoremediationmentioning
confidence: 99%
“…Waste water treatment depends on the precipitation or adsorption of suspended solids, while the use of bio-adsorbent, such as algae, depends on the accumulation of heavy metals (Volesky and Naja 2007). Cyanobacterial approach is an alternative tool for complete removal of heavy metal pollutants with low toxicity due to their cultivate autotrophically and heterotrophically, as well as potential for genetic manipulation (Table 2) (Mitra et al 2012;Sahu 2014).…”
Section: Bioremediation Of Heavy Metalsmentioning
confidence: 99%